Are adverse effects of cannabidiol (CBD) products caused by tetrahydrocannabinol (THC) contamination? [version 6; peer review: 2 approved, 1 approved with reservations] - Stephanie Habel; Frauke Herbi; Dirk W. Lachenmeier; Berit Fischer; Verena Bock; Stephan G. Walch; Yvonne Zerbe; Constanze Sproll; Tabata Rajcic de Rezende (F1000Research, 2023)
Cannabidiol (CBD)-containing products are widely marketed as over the counter products, mostly as food supplements. Adverse effects reported in anecdotal consumer reports or during clinical studies were first assumed to be due to acid-catalysed cyclization of CBD to psychotropic Δ 9tetrahydrocannabinol (Δ9-THC) in the stomach after oral consumption. However, research of pure CBD solutions stored in simulated gastric juice or subjected to various storage conditions such as heat and light with specific liquid chromatographic/tandem mass spectrometric (LC/MS/MS) and ultra-high pressure liquid chromatographic/quadrupole time-of-flight mass spectrometric (UPLC-QTOF) analyses was unable to confirm THC formation. Another hypothesis for the adverse effects of CBD products may be residual Δ9-THC concentrations in the products as contamination, because most of them are based on hemp extracts containing the full spectrum of cannabinoids besides CBD. Analyses of 362 hemp-based products of the German market (mostly CBD oils) confirmed this hypothesis: 39 products (11%) contained Δ9-THC above the lowest observed adverse effect level (2.5 mg/day). Hence, it may be assumed that the adverse effects of some commercial CBD products are based on a low-dose effect of Δ9-THC, with the safety of CBD itself currently being unclear with significant uncertainties regarding possible liver and reproductive toxicity. The safety, efficacy and purity of commercial CBD products is highly questionable, and all of the products in our sample collection showed various non-conformities to European food law such as unsafe Δ9-THC levels, hemp extracts or CBD isolates as non-approved novel food ingredients, non-approved health claims, and deficits in mandatory food labelling requirements. In view of the growing market for such lifestyle products, the effectiveness of the instrument of food business operators' own responsibility for product safety and regulatory compliance must obviously be challenged, and a strong regulatory framework for hemp products needs to be devised.